2018
DOI: 10.1159/000491896
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b Regulates the Mitochondria-Dependent Apoptotic Pathway by Targeting Bax in Doxorubicin Cardiotoxicity

Abstract: Background/Aims: Myocardial apoptosis plays an important role in doxorubicin (Dox) cardiotoxicity. MicroRNA-29 (miR-29) is suggested to function as an anti-fibrotic factor with potential therapeutic effects on cardiac fibrosis. However, it has not been shown whether there is an association between miR-29b and myocardial apoptosis. Methods: Male Wistar rats were transfected with miR-29b agomir by local delivery to the myocardium prior to Dox treatment. Rat cardiomyocytes were pretreated with miR-29b mimics or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…The MiR‐371 family can be used as the plasma biomarkers for monitoring undifferentiated and potentially malignant human pluripotent stem cells (Salvatori et al, ). Besides, some groups have reported that miR‐29b‐3p plays important roles in cell apoptosis, inflammation, and oxidative stress (Jing et al, ; H. Wang et al, ; Xing et al, ; Zhang et al, ). MiR‐29 can be used as a clinical marker of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MiR‐371 family can be used as the plasma biomarkers for monitoring undifferentiated and potentially malignant human pluripotent stem cells (Salvatori et al, ). Besides, some groups have reported that miR‐29b‐3p plays important roles in cell apoptosis, inflammation, and oxidative stress (Jing et al, ; H. Wang et al, ; Xing et al, ; Zhang et al, ). MiR‐29 can be used as a clinical marker of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miR‐29b plays important roles in a variety of diseases (Langsch et al, ; S. Zhou et al, ). This miRNA can prevent doxorubicin‐induced myocardial apoptosis by targeting BAX (Jing, Yang, Jiang, Chen, & Wang, ), inhibit high‐mobility group box 1/TLR4 signallling in liver fibrosis (Zhang et al, ), inhibit breast cancer via targeting the DNA modifying enzyme TET1 (H. Wang et al, ), and alleviate IgAN pathogenesis via targeting the cyclin‐dependent kinase 6 (Xing et al, ). However, there are no reports of the effects of miR‐29b‐3p on II/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Rescue of miR-29b expression in the myocardium resulted in a marked improvement of cardiac function. miR-29b overexpression in rat cardiomyocytes decreased DOX-induced cardiomyocyte apoptosis, since miR-29b targets directly the anti-apoptotic protein Bax [118].…”
Section: Mir-29 Familymentioning
confidence: 94%
“…It was shown that this family is modulated by different anti-cancer treatments. miR-29b is the member of the miR-29 family that was significantly downregulated in myocardium of DOX-treated rats [118]. Rescue of miR-29b expression in the myocardium resulted in a marked improvement of cardiac function.…”
Section: Mir-29 Familymentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of noncoding RNAs about 22 nucleotides in length, which are reported to posttranscriptionally regulate target gene expression by directly binding to 3 ′ -untranslated regions (3 ′ -UTR) of target messenger RNAs [6]. It has been well recognized that a large number of miRNAs participate in regulating doxorubicininduced cardiotoxicity; thus, they could be used as potential cardiotoxicity biomarkers [7].…”
Section: Introductionmentioning
confidence: 99%